Payment under the construction contracts legislation - Pettigrew, Roderick (Thomas Telford, 2005)
This is an authoritative review of current construction industry payment practices under Part II of the Housing Grants Construction and Regeneration Act 1996 for the construction industry. It provides guidance on key features of the Act notably the payment procedures and corresponding structures.